Creativity: Idiographic versus nomothetic approach - Monks, Franz J. (1995)
This article is about the importance of the idiographic approach in the study of the creative- productive individuals. An analysis of Howard Gardner's Creative Minds is carried out, focusing on the seven kinds of intelligence. The life of Sigmund Freud is analyzed as an example of a creative personality with creative achievements, regarding the intrapersonal intelligence. Finally, there is an analysis of the common characteristics among the creative-productive individuals and the determinant factors of their creative exceptional achievements.